1997
DOI: 10.1042/bj3240753
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in effects of insulin-like growth factor I on human osteoblast-like cells

Abstract: The role of insulin-like growth factor I (IGF-I) in extracellular matrix metabolism was studied in both proliferating and confluent human osteoblast-like cultures derived from donors of different ages. In proliferating cultures, recombinant human (rh)IGF-I was found to increase the incorporation of [3H]thymidine in a dose- and age-dependent manner. To study cell proliferation dynamically, continuous growth curves with and without rhIGF-I were modelled by a modified logistic function. Increasing doses of rhIGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 56 publications
1
8
0
2
Order By: Relevance
“…Biglycan mRNA levels were also significantly ( p ≤ 0.01) upregulated, as shown by real-time PCR analysis (Figure 2D ). These data are well in accord with previous reports where IGF-I has been shown to regulate the expression of biglycan in human osteoblast-like cells ( 23 ).…”
Section: Resultssupporting
confidence: 94%
“…Biglycan mRNA levels were also significantly ( p ≤ 0.01) upregulated, as shown by real-time PCR analysis (Figure 2D ). These data are well in accord with previous reports where IGF-I has been shown to regulate the expression of biglycan in human osteoblast-like cells ( 23 ).…”
Section: Resultssupporting
confidence: 94%
“…With aging, tissue responsiveness to IGF‐1 in general is altered. (11–15) Aging is associated with decreases in IGF‐IR and IGF‐IR phosphorylation in muscle,(12) senescence of heart myocytes is accompanied by a reduction in the phosphorylated form of AKT,(13) and in the liver, insulin receptor substrate (IRS) protein levels decrease, and some, but not all investigators, found reduced levels of IGF‐1R. (14) Fibroblast DNA synthesis and proliferation in response to IGF‐1 decrease with age.…”
Section: Introductionmentioning
confidence: 99%
“…Such is the case for osteoblast response to insulin‐like growth factor‐1 (IGF‐1). IGF‐1 receptor levels do not change, but osteoblast response to the growth factor decreases with age [Pfeilschifter et al, 1993, 2000; D'Avis et al, 1997; Ankrom et al, 1998]. In this way, age‐associated shifts in any given factor could be either further enhanced or ameliorated quite locally [Rosen, 2000].…”
Section: Normal and Aging Bone Stroma: A Rich Soil For Cancer Cellsmentioning
confidence: 99%